2012
DOI: 10.1080/09540121.2012.722188
|View full text |Cite
|
Sign up to set email alerts
|

Associations between partner violence perpetration and history of STI among HIV-infected substance using men in Russia

Abstract: Studies document a significant association between victimization from intimate partner violence (IPV) and sexually transmitted infections (STI) and HIV among substance using women in Russia and elsewhere, but no study has examined IPV perpetration and STI among Russian men or HIV-infected men in Eastern Europe. This study was designed to assess the association between lifetime history of IPV perpetration and STI (lifetime and current) among substance using HIV-infected men in Russia. Cross-sectional analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…Consistent with the known literature (11,(22)(23)(24)(25)(26), we also found that MSM engaging in high-risk sexual behaviors such as commercial sex and casual sex, or had a history of STIs are more likely to report IPV victimization. Notably, our findings reveal that young MSM reported more sexual violence than older MSM.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the known literature (11,(22)(23)(24)(25)(26), we also found that MSM engaging in high-risk sexual behaviors such as commercial sex and casual sex, or had a history of STIs are more likely to report IPV victimization. Notably, our findings reveal that young MSM reported more sexual violence than older MSM.…”
Section: Discussionsupporting
confidence: 90%
“…Behavioral evidence has shown that abusive men exhibit a number of HIV-risk behaviors, including having multiple sexual partners, frequent alcohol use, visiting sex workers, and having an STI (Raj et al, 2013; Townsend et al, 2011). Thus, the likelihood of HIV transmission from infected men to women increases through the heightened possibility of physical injury (i.e., tearing or laceration) during forced or non-consensual sexual acts perpetrated by a male partner (Campbell et al, 2013; Silverman et al, 2007; Stockman, Lucea, & Campbell, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in St. Petersburg, alcohol misuse and certain drinking contexts (e.g. on the street) were associated with male IPV perpetration [13, 25]. In St. Petersburg, IDU has been strongly associated with HIV/STIs [26].…”
Section: Introductionmentioning
confidence: 99%
“…As the epidemic in Russia increasingly includes cases of sexually transmitted HIV [20, 23, 25, 26–27], research on sexual risk factors for HIV becomes more important. This study addresses this gap in the field by examining whether history of IPV increases risk for STI and related sexual risk behaviors among HIV-positive female drinkers in Russia.…”
Section: Introductionmentioning
confidence: 99%